Vitamin D deficiency is associated with sudden cardiac death, combined cardiovascular events, and mortality in haemodialysis patients - Drechsler, Christiane; Pilz, Stefan; Obermayer-Pietsch, Barbara; Verduijn, Marion; Tomaschitz, Andreas; Krane, Vera; Espe, Katharina; Dekker, Friedo; Brandenburg, Vincent; März, Winfried; Ritz, Eberhard; Wanner, Christoph (European heart journal, 2010)
Dialysis patients experience an excess mortality, predominantly of sudden cardiac death (SCD). Accumulating evidence suggests a role of vitamin D for myocardial and overall health. This study investigated the impact of vitamin D status on cardiovascular outcomes and fatal infections in haemodialysis patients.25-hydroxyvitamin D [25(OH)D] was measured in 1108 diabetic haemodialysis patients who participated in the German Diabetes and Dialysis Study and were followed up for a median of 4 years. By Cox regression analyses, we determined hazard ratios (HR) for pre-specified, adjudicated endpoints according to baseline 25(OH)D levels: SCD (n = 146), myocardial infarction (MI, n = 174), stroke (n = 89), cardiovascular events (CVE, n = 414), death due to heart failure (n = 37), fatal infection (n = 111), and all-cause mortality (n = 545). Patients had a mean age of 66 ± 8 years (54% male) and median 25(OH)D of 39 nmol/L (interquartile range: 28-55). Patients with severe vitamin D deficiency [25(OH)D of≤ 25 nmol/L] had a 3-fold higher risk of SCD compared with those with sufficient 25(OH)D levels >75 nmol/L [HR: 2.99, 95% confidence interval (CI): 1.39-6.40]. Furthermore, CVE and all-cause mortality were strongly increased (HR: 1.78, 95% CI: 1.18-2.69, and HR: 1.74, 95% CI: 1.22-2.47, respectively), all persisting in multivariate models. There were borderline non-significant associations with stroke and fatal infection while MI and deaths due to heart failure were not meaningfully affected.Severe vitamin D deficiency was strongly associated with SCD, CVE, and mortality, and there were borderline associations with stroke and fatal infection. Whether vitamin D supplementation decreases adverse outcomes requires further evaluation.